2004
DOI: 10.3201/eid1012.040511
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Viremia in Wild Rock Pigeons

Abstract: Feral rock pigeons were screened for neutralizing antibodies to West Nile virus (WNV) during late winter/spring and summer of 2002 and 2003. Additionally, virus isolation from serum was attempted from 269 birds collected during peak transmission periods. The observed viremia levels and seroprevalence indicate that this species could be involved in amplifying WNV in urban settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 13 publications
1
23
0
2
Order By: Relevance
“…7 In addition, both passive dead bird surveillance as well as active live bird surveillance have also indicated consistent yearly WNV infection among avian hosts in Atlanta at levels consistent with rates found in other urban centers such as Chicago. [7][8][9][10][11] However, a total of only 330 human cases have been reported in Georgia since 2001 (incidence of 3.3 per 100,000), in contrast to the 2,088 human cases from Illinois since 2002 (incidence of 16.2 per 100,000). 2 With trends in the enzootic infection levels among hosts and vectors in Atlanta similar to those seen in cities with five times the human incidence, the reason for the lack of human WNV spillover in Atlanta and the southeastern region in general has remained unclear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 In addition, both passive dead bird surveillance as well as active live bird surveillance have also indicated consistent yearly WNV infection among avian hosts in Atlanta at levels consistent with rates found in other urban centers such as Chicago. [7][8][9][10][11] However, a total of only 330 human cases have been reported in Georgia since 2001 (incidence of 3.3 per 100,000), in contrast to the 2,088 human cases from Illinois since 2002 (incidence of 16.2 per 100,000). 2 With trends in the enzootic infection levels among hosts and vectors in Atlanta similar to those seen in cities with five times the human incidence, the reason for the lack of human WNV spillover in Atlanta and the southeastern region in general has remained unclear.…”
Section: Introductionmentioning
confidence: 98%
“…WNV was confirmed in these samples by reverse transcription polymerase chain reaction (PCR), using degenerate WNV-specific primers amplifying a 376-base fragment spanning the nucleocapsid and premembrane genes, as described in Allison and others. 8 Mosquito blood-meal analysis. Bloodfed mosquitoes were analyzed to determine the vertebrate species identity of the mosquito's blood meal.…”
Section: Methodsmentioning
confidence: 99%
“…4 Previous research has shown that virus levels are not amplified to the same degree in all bird species, and mosquito species can vary greatly in their competence as efficient vectors. [5][6][7][8][9][10][11] In the eastern United States, two closely related mosquito species, Culex pipiens and Culex restuans, have been implicated as being among the most important WNV vectors. Both species have adapted well to urban areas and are strongly ornithophilic (bird loving) in their feeding preferences.…”
mentioning
confidence: 99%
“…Son estos vertebrados los hospedadores definitivos y amplificadores primarios del virus así como los principales diseminadores (Malkinson & Banet, 2002), reintroduciendo ocasionalmente el virus en las zonas templadas cuando regresan de sus áreas de invernada en las que éste es endémico (Nasci et al 2001), aunque también se ha aislado el virus en aves residentes y sinantrópicas como Columbiformes (Allison et al 2004). Muchas especies de aves migran para aprovecharse de las diferencias estacionales de temperatura en el mundo, con lo que optimizan la disponibilidad de fuentes de alimento y de hábitats reproductivos; no obstante el proceso acarrea una serie de riesgos tales como la predación, el parasitismo y hasta la muerte (Lotta-Aré-valo, 2010).…”
Section: Resultados Y Discusiónunclassified